The The Influence of Readers’ Cultural Values on the Interpretation of Indonesian and English Folktales - Andi Inayah Soraya; Burhanuddin Arafah; Herawaty Abbas; Rezky Ramadhani (Universitas Cokroaminoto Palopo, 2025)
This study examines readers’ responses to two folktales Timun Mas (Indonesia) and Jack and the Beanstalk (England) with the objective of identifying how cultural values shape intellectual and emotional engagement with narrative texts. Data were collected from 30 undergraduate students majoring in English literature. Employing an experimental approach, participants read both folktales and responded through structured questionnaires and open-ended written reflections. The findings reveal notable variations in readers’ interpretations of the two stories. In Timun Mas, participants expressed both positive and negative responses influenced by their cultural backgrounds. Many appreciated the integration of Javanese cultural elements such as the naming of characters, the inclusion of traditional objects like terasi (shrimp paste), and references to takhyul (superstition) which contributed to the story’s cultural richness and authenticity. Readers also admired Timun Mas’s perseverance in confronting adversity, reflecting cultural values of resilience and moral strength. Conversely, some participants criticized the character of Mbok Srini for breaking her promise to the giant, viewing this act as inconsistent with ethical principles valued in their own culture. In contrast, responses to Jack and the Beanstalk were predominantly negative, with readers interpreting Jack’s actions as morally questionable. Many described him as greedy, deceitful, and unjustified in killing the giant. Several participants suggested that the story should have concluded with a tragic ending in which Jack faces the consequences of his actions. Overall, the study underscores the profound influence of cultural background on readers’ moral evaluations, emotional responses, and interpretive engagement with folktales across different cultural traditions.